Recent engineering practices: mechanical and manufacturing field - Abdullah, Rohana (Penerbit UTeM Press, 2023)
Recent Engineering Practices is designed to assist readers with science, mathematics, engineering and technology background to resolve manufacturing industry issues. The book covers the management of manufacturing constraints, ergonomics and material management. Readers will learn about new material applications and the development of nanoparticle technology.